2012
DOI: 10.1016/j.pbb.2011.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Diminished conditioned responding to the nicotine stimulus by antidepressant drugs with differing specificity for the serotonin and norepinephrine transporter

Abstract: People diagnosed with depression also tend to have a co-morbid nicotine addiction. Thus, there is interest in whether medications used to treat depression alter the effects of nicotine. This study assessed whether the antidepressant drugs citalopram, imipramine, and reboxetine, with differing specificity for the serotonin and norepinephrine transporter, altered responding controlled by the conditional stimulus (CS) effects of nicotine. Rats received intermixed 20-min nicotine (0.4 mg base/kg, SC) and saline se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The 0.05 mg/kg dose was selected for that experiment because it prompted partial substitution for the nicotine CS in a wide range of studies. Further, this dose is on the lower end of the range of median effective doses (ED 50 ) reported when the 0.4 mg/kg nicotine served as the CS (range = 0.033-0.099 mg/kg; mean = 0.072 mg/kg; see Murray et al, 2007aMurray et al, , 2007bStruthers et al, 2009;Murray et al, 2010;Reichel et al, 2010;Wilkinson et al, 2010;Dion et al, 2012). The 0.05 mg/kg dose of nicotine evoked a partial goal-tracking CR in the first five of the six 20-min extinction sessions.…”
mentioning
confidence: 99%
“…The 0.05 mg/kg dose was selected for that experiment because it prompted partial substitution for the nicotine CS in a wide range of studies. Further, this dose is on the lower end of the range of median effective doses (ED 50 ) reported when the 0.4 mg/kg nicotine served as the CS (range = 0.033-0.099 mg/kg; mean = 0.072 mg/kg; see Murray et al, 2007aMurray et al, , 2007bStruthers et al, 2009;Murray et al, 2010;Reichel et al, 2010;Wilkinson et al, 2010;Dion et al, 2012). The 0.05 mg/kg dose of nicotine evoked a partial goal-tracking CR in the first five of the six 20-min extinction sessions.…”
mentioning
confidence: 99%
“…Ligands that act, in part, by inhibiting monoamine transporters interfere with nicotine-evoked goal-tracking and nicotine self-administration (Di Chiara, 2000; Dion et al , 2012; Rauhut et al , 2003; Wilkinson et al , 2010). Thus, the impact of iptakalim per se on dopamine and serotonin transporter function was evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…For example, bupropion, a dopamine transporter inhibitor, fully substitutes for the stimulus effects of nicotine. Conversely, the SERT inhibitor, citalopram, blocks the conditioned response controlled by the nicotine stimulus (Dion et al , 2012). However, since iptakalim did not appreciably inhibit SERT or DAT function, another mechanism(s) likely underlies its effects on the stimulus and reinforcing effects of nicotine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite having apparent limited success in very early clinical studies [ 91 ], recent preclinical studies indicate that it may be more efficacious with regards to the modulating the affective aspects of nicotine intake. A study in rodents identified a decrease in conditioned responding to the nicotine CS and thus reducing incentive value of drug administered [ 92 ]. An analogue of imipramine, has also shown recent success preclinically [ 93 ].…”
Section: Tricyclic Antidepressantsmentioning
confidence: 99%